2003
DOI: 10.1097/01.ju.0000063640.41307.c9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Radiation Induced Hemorrhagic Cystitis With Hyperbaric Oxygen.

Abstract: Hyperbaric oxygen therapy for radiation induced hemorrhagic cystitis is an efficacious treatment modality for patients in whom other forms of management have failed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
0
8

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 14 publications
4
74
0
8
Order By: Relevance
“…Severe RTOG/EORCT grade III or worse bladder morbidity has been reported at 1% at 5 years, 1.4% at 10 years and 2.3% at 20 years following radiotherapy for cervical cancer (20). Radiation for prostate cancer may lead to moderate or severe haematuria in 3-5% of cases (10,12).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Severe RTOG/EORCT grade III or worse bladder morbidity has been reported at 1% at 5 years, 1.4% at 10 years and 2.3% at 20 years following radiotherapy for cervical cancer (20). Radiation for prostate cancer may lead to moderate or severe haematuria in 3-5% of cases (10,12).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some of them may have serious systematic side effects or may exacerbate bladder fibrosis which was initiated by radiation treatment, leading to a small-capacity bladder (1,(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). A recent Cochrane Database systematic literature review on non-surgical interventions for late radiation cystitis in patients who have received radical radiotherapy to the pelvis concluded that in the absence of randomized controlled studies it is impossible to set definitive rules for treatment (21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hyperbaric oxygen therapy for HC patients has achieved encouraging success with no adverse effects in recent years, 25 especially for the patients induced from radiation, 40 which allows better tissue diffusion of oxygen, improving neoangiogenesis by increasing the vascular density of irradiated tissues. However, the wide application of this approach is limited by the requirement of a hyperbaric chamber and long procedure (20-30 days).…”
Section: Discussionmentioning
confidence: 99%